Antioxidant effect of acerola fruit powder, rosemary and licorice extract in caiman meat nuggets containing mechanically separated caiman meat - de Paiva, Gilmar Borges [UNESP]; Trindade, Marco Antonio; Romero, Javier Telis [UNESP]; da Silva-Barretto, Andrea Carla [UNESP] (Elsevier, 2021)
The aim of this work was to evaluate the antioxidant effect of acerola fruit powder, rosemary and licorice extract in caiman meat nuggets containing high amounts of mechanically separated caiman meat (MSCM) during 120 days of frozen storage. Five treatments were prepared: a control without antioxidant (CON), sodium erythorbate at 500 mg/kg (ERY), acerola fruit powder at 500 mg/kg (AFP), with licorice extract at 500 mg/kg (LIE) and rosemary extract at 500 mg/kg (ROE). The addition of natural antioxidants increased color, cohesiveness, and decreased TBARS values. The redness values were higher for LIE and these values were different to the CON. Nuggets with licorice extract had significantly lower TBARS values at the end of the storage period compared to the control. All the treatments were similar in sensory analysis, with good acceptability. These results indicate licorice extract used in caiman meat nuggets containing a high amount of MSCM caiman has the potential to improve quality during frozen storage.
Keywords: Caiman; Color parameters; Exotic meat products; Lipid oxidation; Sensory acceptance